Investigation of praseodymium and samarium co-doped ceria as an anode catalyst for DIR-SOFC fueled by biogas. (30th October 2020) - Bochentyn, B.; Błaszczak, P.; Gazda, M.; Fuerte, A.; Wang, S.-F.; Jasiński, P.
Abstract: The Pr and Sm co-doped ceria (with up to 20 mol.% of dopants) compounds were examined as catalytic layers on the surface of SOFC anode directly fed by biogas to increase a lifetime and the efficiency of commercially available DIR-SOFC without the usage of an external reformer. The XRD, SEM and EDX methods were used to investigate the structural properties and the composition of fabricated materials. Furthermore, the electrical properties of SOFCs with catalytic layers deposited on the Ni-YSZ anode were examined by a current density-time and current density-voltage dependence measurements in hydrogen (24 h) and biogas (90 h). Composition of the outlet gasses was in situ analysed by the FTIR-based unit. It has been found out that Ce0.9 Sm0.1 O2-δ and Ce0.8 Pr0.05 Sm0.15 O2-δ catalytic layers show the highest stability over time and thus are the most attractive candidates as catalytic materials, in comparison with other investigated lanthanide-doped ceria, enhancing direct internal reforming of biogas in SOFCs. Graphical abstract: Image 1 Highlights: Pr and Sm co-doped ceria synthesized by reverse microemulsion method. Composition of outlet gases analyzed by Fourier Transformed Infrared Spectroscopy. Ce0.9 Sm0.1 O2-δ  and Ce0.8 Pr0.05 Sm0.15 O2-δ  - attractive catalysts for DIR- SOFC.